2010
DOI: 10.1103/physrevd.82.103533
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bayesian model averaging to measurements of the primordial power spectrum

Abstract: Cosmological parameter uncertainties are often stated assuming a particular model, neglecting the model uncertainty, even when Bayesian model selection is unable to identify a conclusive best model. Bayesian model averaging is a method for assessing parameter uncertainties in situations where there is also uncertainty in the underlying model. We apply model averaging to the estimation of the parameters associated with the primordial power spectra of curvature and tensor perturbations. We use COSMONEST and MULT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…The notion of Bayesian doubt, introduced in [ 624 ], can also be used to extend the power of Bayesian model selection to the space of unknown models in order to test our paradigm of a ΛCDM cosmological model. Bayesian model averaging [ 571 , 709 ] can also be used to obtain final inferences parameters which take into account the residual model uncertainty. Due to the concentration of probability mass onto simpler models (as a consequence of Occam’s razor), Bayesian model averaging can lead to tighter parameter constraints than non-averaged procedures, for example on the curvature parameter [ 917 ].…”
Section: Statistical Methods For Performance Forecastsmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of Bayesian doubt, introduced in [ 624 ], can also be used to extend the power of Bayesian model selection to the space of unknown models in order to test our paradigm of a ΛCDM cosmological model. Bayesian model averaging [ 571 , 709 ] can also be used to obtain final inferences parameters which take into account the residual model uncertainty. Due to the concentration of probability mass onto simpler models (as a consequence of Occam’s razor), Bayesian model averaging can lead to tighter parameter constraints than non-averaged procedures, for example on the curvature parameter [ 917 ].…”
Section: Statistical Methods For Performance Forecastsmentioning
confidence: 99%
“…Bayesian model averaging [ 571 , 709 ] can also be used to obtain final inferences parameters which take into account the residual model uncertainty. Due to the concentration of probability mass onto simpler models (as a consequence of Occam’s razor), Bayesian model averaging can lead to tighter parameter constraints than non-averaged procedures, for example on the curvature parameter [ 917 ].…”
Section: Statistical Methods For Performance Forecastsmentioning
confidence: 99%
“…Parkinson and Liddle [53] applied Bayesian model averaging to measurements of the parameters of the primordial power spectrum of density fluctuations. They considered five different models.…”
Section: Applications In Astrophysicsmentioning
confidence: 99%
“…The top label denotes the Bayes factor of the n run -model compared to the power-law n s -model, using current observations. as used by [24]. Figure 4 shows the 1D and 2D marginalised posterior distributions for the inflationary parameters, using current experiments (black line): n s = 0.985 ± 0.017, n run = −0.043 ± 0.018 and r run < 0.324; and Planck (red line) and CMBPol (green line) realisations.…”
Section: Running Scalar Spectral-indexmentioning
confidence: 99%
“…with WMAP7+QUaD [4]. It has also been shown that the existence of a turn-over in P R (k), by using model-independent techniques, is preferred [14,15,24,32].…”
Section: Introductionmentioning
confidence: 99%